1964
DOI: 10.1139/v64-421
|View full text |Cite
|
Sign up to set email alerts
|

THE INHIBITION OF AUTOXIDATION BY 2,4,6-TRI-tert-BUTYL SUBSTITUTED PHENOL, ANILINE, AND THIOPHENOL

Abstract: The reactions of peroxy radicals with 2,4,6-tri-t-butyl substituted phenol, aniline, and thiophenol have been examined by a kinetic method. The primary process involves abstraction of the hydrogen atom attached to the functional group, since all three compounds show fairly large isotope effects when this hydrogen is replaced by deuterium. The phenol and aniline react with about two peroxy radicals per molecule. In contrast, the thiophenol reacts with only a single peroxy radical. ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Aforementioned discussion proves that the main reactive radical accounting for SMX degradation in the Co/PAA process was R–O • rather than HO • . The detected hydroxyl-SMX derivative (TP-270) after reaction indicated hydroxylation reaction took place on the aniline ring, which would be explained by the formation of aniline radicals via hydrogen atom abstraction by peroxyl radicals (pathway I) . SMX can be also oxidized to nitroso-SMX (TP-268) which can be further converted to nitro-SMX, indicating that the −NH 2 group contained in SMX is vulnerable to R–O • in the Co/PAA process (pathway II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aforementioned discussion proves that the main reactive radical accounting for SMX degradation in the Co/PAA process was R–O • rather than HO • . The detected hydroxyl-SMX derivative (TP-270) after reaction indicated hydroxylation reaction took place on the aniline ring, which would be explained by the formation of aniline radicals via hydrogen atom abstraction by peroxyl radicals (pathway I) . SMX can be also oxidized to nitroso-SMX (TP-268) which can be further converted to nitro-SMX, indicating that the −NH 2 group contained in SMX is vulnerable to R–O • in the Co/PAA process (pathway II).…”
Section: Resultsmentioning
confidence: 99%
“…The detected hydroxyl-SMX derivative (TP-270) after reaction indicated hydroxylation reaction took place on the aniline ring, which would be explained by the formation of aniline radicals via hydrogen atom abstraction by peroxyl radicals (pathway I). 68 SMX can be also oxidized to nitroso-SMX (TP-268) which can be further converted to nitro-SMX, indicating that the −NH 2 group contained in SMX is vulnerable to R−O • in the Co/PAA process (pathway II). Meanwhile, a number of dimeric products were identified, illustrating coupling reaction also occurred during the degradation of SMX in the Co/PAA process (pathway III).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Although thiols have relatively weak S−H bonds (87 kcal/ mol) 4 and are highly useful HAT reagents in organic synthesis (mainly to reduce alkyl radicals, k = 1 × 10 7 M −1 s −1 ), 25 they are comparatively poor H-atom donors to peroxyl radicals, and the propensity of the product thiyl radicals to dimerize and react with O 2 generally limits the stoichiometry of their RTA reactions to (at most) a single peroxyl radical. 26 While studying the antioxidant mechanism of allicin, the characteristic odorous thiosulfinate from garlic (vide infra), we uncovered the impressive HAT chemistry of sulfenic acids (RSOH). Sulfenic acids arise from the two-electron oxidation of thiols, 27 which reduces the strength of the bond to the labile H-atom from ∼87 kcal/mol 4 to ∼70 kcal/mol 28,29 (Figure 5).…”
Section: ■ Organosulfur Antioxidantsmentioning
confidence: 99%
“…This is based on sulfur’s relatively high nucleophilicity and oxidizability to acids that are capable of dehydrating and/or cleaving peroxides in Hock-like processes. Although thiols have relatively weak S–H bonds (87 kcal/mol) and are highly useful HAT reagents in organic synthesis (mainly to reduce alkyl radicals, k = 1 × 10 7 M –1 s –1 ), they are comparatively poor H-atom donors to peroxyl radicals, and the propensity of the product thiyl radicals to dimerize and react with O 2 generally limits the stoichiometry of their RTA reactions to (at most) a single peroxyl radical …”
Section: Organosulfur Antioxidantsmentioning
confidence: 99%
“…Conventional kinetic studies have shown that overall rates of hydrocarbon autoxidation inhibited by 2,6-di-tert-butyl-4-substit~1ted phenols are proportional to the rate of chain initiation and inversely proportional to the phenol concentration (8, [10][11][12][13][14]. This implies that reaction of a chain carrying alkylperoxy radical and a phenol is bimolecular.…”
Section: 6-di-tert-butyl-4-s~bstit~1te~i Pl~enolsmentioning
confidence: 99%